Chemical identification and quality evaluation of Lycopus lucidus Turcz by UHPLC‐Q‐TOF‐MS and HPLC‐MS/MS and hierarchical clustering analysis. (20th November 2016) - Ren, Qiang; Ding, Lin; Sun, Shan‐shan; Wang, Hui‐yun; Qu, Liang
Abstract: Lycopus lucidus Turcz has been used as a traditional phytomedicine for menstrual disorder, amenorrhea, menstrual cramps, inflammation and cardiovascular diseases. However, there is not enough information about identification and quantification for the chemical constituents of L. lucidus Turcz. In this work, a simple, rapid and sensitive UHPLC‐Q‐TOF‐MS method was developed for characterization and identification of the phytochemical compositions in L. lucidus Turcz in negative ion mode. A total of 37 compounds, including 15 phenolic acids, 12 flavonoids, three triterpenoids and seven organic acids were tentatively characterized and identified by means of the retention time, accurate mass and characteristic fragment ions. Thirteen compounds were reported for the first time in L. lucidus Turcz. Among of them, 11 compounds were further quantified by multiple reactions monitoring. The results showed good performance with respect to linearity ( r  > 0.9959), repeatability (RSD < 2.6%), intra‐ and inter‐day precision (RSD < 3.2%), recovery (93.1–104.9%), and lower limit of quantification (5–50 ng/mL). Subsequently, the results were analyzed and classified by hierarchical cluster analysis. The research could be applied for identification and quality evaluation for L. lucidus Turcz.